2018
DOI: 10.1002/jhet.3187
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted Synthesis of Hybrid Heterocyclics as Biological Potent Molecules

Abstract: A series of novel 5‐((1H‐benzo[d]imidazol‐2‐yl)methyl)‐2‐((3aR,5S,6S,6aR)‐2,2‐dimethyl‐6‐((1‐phenyl‐1H‐1,2,3‐triazol‐4‐yl)methoxy)tetrahydrofuro[2,3‐d][1,3]dioxol‐5‐yl)‐3‐phenylthiazolidin‐4‐ones 9a–n has been synthesized from triazole‐linked thiazolidinone derivatives 8a–g with o‐phenylenediamine and characterized by IR, NMR, MS, and elemental analyses. Further, these compounds were screened for their antibacterial activity against Gram‐positive bacteria, namely, Bacillus subtilis (ATCC 6633), Staphylococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Tiwari and co-workers [41] reported the synthesis of a series of glycosyl triazoles and their evaluation as efficient ligands in Cheteroatom coupling reactions by using a mono-O-isopropylidene glucofuranose derivative as starting material. Srinivas et al [42,43] reported a 1,2,3-triazole-linked allofuranose compound that can be a key intermediary in the preparation of a series of heterocyclic-containing carbohydrate-triazole hybrids with potential antimicrobial activity. The synthesis of such compounds involves a selective acidic hydrolysis of the corresponding acetonide to yield a chiral diol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiwari and co-workers [41] reported the synthesis of a series of glycosyl triazoles and their evaluation as efficient ligands in Cheteroatom coupling reactions by using a mono-O-isopropylidene glucofuranose derivative as starting material. Srinivas et al [42,43] reported a 1,2,3-triazole-linked allofuranose compound that can be a key intermediary in the preparation of a series of heterocyclic-containing carbohydrate-triazole hybrids with potential antimicrobial activity. The synthesis of such compounds involves a selective acidic hydrolysis of the corresponding acetonide to yield a chiral diol.…”
Section: Resultsmentioning
confidence: 99%
“…Srinivas et al . [ 42 , 43 ] reported a 1,2,3-triazole-linked allofuranose compound that can be a key intermediary in the preparation of a series of heterocyclic-containing carbohydrate–triazole hybrids with potential antimicrobial activity. The synthesis of such compounds involves a selective acidic hydrolysis of the corresponding acetonide to yield a chiral diol.…”
Section: Resultsmentioning
confidence: 99%
“…Following the successful introduction of antimicrobial and nematicidal agents, inspired by the biological profile of triazoles, thiazolidenones, and in the continuation of our work on biologically active heterocycles, [27][28][29][30][31][32][33][34][35][36][37][38][39] we have developed a series of novel triazole linked thiazolidenone derivatives, and evaluated their nematicidal activity along with antibacterial activity.…”
Section: Srinivas Et Al: Synthesis and Biological Evaluation mentioning
confidence: 99%
“…Following the successful introduction of antimicrobial and nematicidal agents, inspired by the biological profile of triazoles, thiazolidinones, isoxazoles, and their increasing importance in pharmaceutical and biological fields and in continuation of our work on biological active molecules and in order to enhance the biological activity of triazoles, thiazolidinones and isoxazoles moieties, it was thought to interest to accommodate triazole, thiazolidinones, and isoxazoles moieties in single molecular framework. In this article, we wish to report the synthesis of a new class of hybrid heterocyclics 10a–g in good yields and their evaluated in vitro antifungal and nematicidal activity.…”
Section: Introductionmentioning
confidence: 99%